Palestinian Art : From 1850 to the Present. - Boullata, Kamal; Berger, John (London : Saqi, 2009)
Saig , Nicola; Abu Shaqra , Asim ; Khoury , Sari ; Shibli , Ahlam ; Halaby , Sophie
Kunst in Palestina 20ste eeuw
boek